2017
DOI: 10.5897/ajar2017.12418
|View full text |Cite
|
Sign up to set email alerts
|

Response of Eleusine indica to herbicides and N fertilizer in dry seeded rice

Abstract: Weed has become one of the most serious problems in dry seeded rice (DSR). To increase the competitiveness with weeds and achieve the optimum growth of rice, weed management in DSR needs an integration of herbicides and optimum nitrogen (N) fertilizer rates. In this study, the bioassay species were treated with a series of pre-emergence (pretilachlor and pendimethalin) and early post-emergence (propanil+thiobencarb) herbicide concentrations and N fertilizer. It was found that pretilachlor at an application rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…In our study, the optimum rate of c to fully suppress the shoot growth of E. indica was 2.5 kg ai/ha (Fig. 4 ) whilst the early post-emergence study of rice herbicide, propanil combined with thiobencarb at 3.6 kg ai/ha conducted by Norhafizah et al 29 was found to decrease the shoot fresh weight of E. indica greater than 90%. Although diuron fully inhibited the shoot growth of O. verticillata at the beginning first week of all treatments, the seedlings treated by compound c was still able to grow (data not shown).…”
Section: Discussionmentioning
confidence: 46%
“…In our study, the optimum rate of c to fully suppress the shoot growth of E. indica was 2.5 kg ai/ha (Fig. 4 ) whilst the early post-emergence study of rice herbicide, propanil combined with thiobencarb at 3.6 kg ai/ha conducted by Norhafizah et al 29 was found to decrease the shoot fresh weight of E. indica greater than 90%. Although diuron fully inhibited the shoot growth of O. verticillata at the beginning first week of all treatments, the seedlings treated by compound c was still able to grow (data not shown).…”
Section: Discussionmentioning
confidence: 46%
“…Weeds are capable of absorbing nutrients faster and in relatively bigger amounts than crop plants (Blackshaw, 2005), and in the presence of a high weed population density, fertilizer application may stimulate weed growth greatly over the crop growth (Mahajan et al, 2009). In contrast, previous study found that the addition of N fertilizer reduces the weed emergence in aerobic rice system where the soil N level was altered (Norhafizah et al, 2017). In addition, Singh et al (2014) has stated that increased nitrogen rate more than 180 kg ha -1 decreases the weed density of grasses, sedges and broadleaf.…”
Section: Introductionmentioning
confidence: 75%
“…Soil N level may alter the weed community structure which specifies the failure of herbicide alone to control the respective weeds (Cathcart et al, 2004). Norhafizah et al (2017) stated that application of N fertiliser at an application rate of 50, 100 and 150 kg ha -1 influences the soil environment and improve herbicide efficacy to suppress the emergence and shoot fresh weight of E. indica. Irrespective of fertiliser, the present study found that the emergence and shoot fresh weight of E. indica decreases with increasing N rate.…”
Section: Effect Of N Fertiliser On Weed Growthmentioning
confidence: 99%